A comparison on the percentage of polymerase chain reaction positivity for SARS-CoV-2 between Public Health Center referrals and direct walk-in patients: A single center retrospective analysis in Tokyo. Issue 6 (June 2021) - Nakajima, Mikio; Yamamoto, Yasuhiro; Kaszynski, Richard H.; Yamauchi, Yuko; Yamamoto, Kazuo; Nakajima, Yasushi; Goto, Hideaki; Yamaguchi, Yoshihiro; Ide, Takafumi; Maeda, Yoshiharu; Tajiri, Yasuhito
Abstract: Introduction: The Public Health Center (PHC)—known as hokenjo in Japan—assume a crucial role in disease control. Coronavirus disease 2019 (COVID-19) is one of many designated infectious diseases monitored by the agency. During the present pandemic, patients who suspected COVID-19 were instructed to call the Coronavirus Consultation Center in the PHC prior to visiting the hospital. The aim of this study was to elucidate the differences in polymerase chain reaction (PCR) positivity between PHC referrals and direct walk-in patients. Methods: The present was a single-center, retrospective cohort study conducted at the Tokyo Metropolitan Hospital from March to September, 2020. Patients who received a PCR test for SARS-CoV-2 were included and categorized into the PHC referral or direct walk-in groups. The outcomes included the total number of patients undergoing PCR tests and the percentage of PCR positivity in each group. Results: We identified 1680 patients (781 PHC referred and 899 direct walk-in groups). The percentage of PCR positivity did not significantly differ between the PHC referral and direct walk-in groups during the first wave (30.5% vs. 29.2%; p = 0.78). PCR positivity was significantly higher in the PHC referral group than the direct walk-in group during the second wave (30.1% vs. 23.1%; p = 0.051) and entire study period (30.2% vs. 24.7%; p = 0.011). Conclusions: Despite health authority recommendations, the number of direct walk-in patients were higher than PHC referral patients. The percentage of PCR positivity was significantly higher in the PHC referral group than in the direct walk-in group.